2011
DOI: 10.1590/s1516-89132011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biodiversity from an anaerobic up flow bioreactor with ANAMMOX activity inoculated with swine sludge

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Previous phylogenetic analysis based on 16S rRNA genes indicated that Jettenia was most closely related (98% similarity of 16S rRNA gene) to an anammox bacterium strain called KSU-1 (Quan et al, 2008 ; Viancelli et al, 2011 ). Additionally, the HZS subunit A ( hzsA ), a phylomarker for anammox bacteria, of Jettenia and KSU-1 shared 92.8% sequence identity on nucleotide level and 97.0% on amino acid level, which was much higher than any other pair of anammox bacteria (Harhangi et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous phylogenetic analysis based on 16S rRNA genes indicated that Jettenia was most closely related (98% similarity of 16S rRNA gene) to an anammox bacterium strain called KSU-1 (Quan et al, 2008 ; Viancelli et al, 2011 ). Additionally, the HZS subunit A ( hzsA ), a phylomarker for anammox bacteria, of Jettenia and KSU-1 shared 92.8% sequence identity on nucleotide level and 97.0% on amino acid level, which was much higher than any other pair of anammox bacteria (Harhangi et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…In studies by VIANCELLI et al (2011), in which partial nitritation and anammox activity occurred in the same reactor submitted to DO values lower than 0.5 mg L −1 , process viability was confirmed under low dissolved oxygen concentration. In experiments with complete nitrification, ANDRADE et al (2010) assessed the influence of DO on nitrification speed and observed that nitrification rate is directly proportional to DO concentration.…”
Section: Introductionmentioning
confidence: 92%
“…The factors that exert a greater influence on this inhibition are pH, dissolved oxygen (DO), temperature and nitrifying bacteria (Nitrosomonas and Nitrobacter) doubling rate (PRA et al, 2012;VIANCELLI et al, 2011;SUN et al 2010, ZHU et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Sejak penemuannya pada tahun 1995, proses anammox dalam siklus nitrogen biologis terus dilakukan eksplorasi. Saat ini, terdapat 7 genus bakteri anammox, yaitu Candidatus Brocadia (6) , Candidatus Kuenenia (7) , Candidatus Scalindua (8) , Candidatus Anammoxoglobus (9) , Candidatus Jettenia (10) , Canditatus Brasilis (11) dan Candidatus Anammoximicrobium (12) dengan jumlah 22 spesies (13) akan tetapi tidak satupun genus atau spesies yang dilaporkan ditemukan di Indonesia. Indonesia sebagai negara tropis yang terkenal dengan keanekaragaman hayati dan mikroba memiliki potensi ditemukannya bakteri anammox.…”
Section: Latar Belakangunclassified